Certification and integration of management systems: the experience of Portuguese small and medium enterprises - Santos, Gilberto (2013)
The purpose of this study was to characterize the situation of Portuguese Small and Medium Enterprises (SMEs) concerning the certification of their Quality Management Systems (QMS), Environmental Management Systems (EMS) and Occupational Health and Safety Management Systems (OHSMS), in their individually form, to identify benefits, drawbacks and difficulties associated with the certification process and to characterize the level of integration that has been achieved. This research was based on a survey carried out by the research team; it was administered to 46 Portuguese SMEs. Our sample comprised 20 firms (43%) from the Trade/Services activity sector, 17 (37%) from the Industrial sector, 5 (11%) from the Electricity/Telecommunications sector and 4 (9%) from the Construction area. All SMEs surveyed were certified according to the ISO 9001 (100%), a quarter of firms were certified according to the ISO 14001 (26.1%) and a few certified by OHSAS 18001 (15.2%). We undertook a multivariate cluster analysis, which enabled grouping variables into homogeneous groups or one or more common characteristics of the SMEs participating in the study. Results show that the main benefits that Portuguese SMEs have gained from the referred certifications have been, among others, an improvement of both their internal organization and external image. We also present the main difficulties in achieving certification. Overall, 7 of the Portuguese SMEs examined indicated that the main benefits of the IMS implementation management included costs reduction, increased employee training and easier compliance of legislation. The respective drawbacks and difficulties are also presented. Finally, we presented the main integrated items in the certified Portuguese SMEs we examined.